Influence of Confounding Factors on Radiation Dose Estimation Using In Vivo Validated Transcriptional Biomarkers. Issue 1 (July 2018) - Cruz-Garcia, Lourdes; O'Brien, Grainne; Donovan, Ellen; Gothard, Lone; Boyle, Sue; Laval, Antoine; Testard, Isabelle; Ponge, Lucyna; Woźniak, Grzegorz; Miszczyk, Leszek; Candéias, Serge M.; Ainsbury, Elizabeth; et al.
Abstract : Abstract: For triage purposes following a nuclear accident, blood-based gene expression biomarkers can provide rapid dose estimates for a large number of individuals. Ionizing-radiation-responsive genes are regulated through the DNA damage-response pathway, which includes activation of multiple transcription factors. Modulators of this pathway could potentially affect the response of these biomarkers and consequently compromise accurate dose estimation calculations. In the present study, four potential confounding factors were selected: cancer condition, sex, simulated bacterial infection (lipopolysaccharide), and curcumin, an anti-inflammatory/antioxidant agent. Their potential influence on the transcriptional response to radiation of the genes CCNG1 and PHPT1, two biomarkers of radiation exposure ex vivo, was assessed. First, both CCNG1 and PHPT1 were detected in vivo in blood samples from radiotherapy patients and as such were validated as biomarkers of exposure. Importantly, their basal expression level was slightly but significantly affected in vivo by patients' cancer condition. Moreover, lipopolysaccharide stimulation of blood irradiated ex vivo led to a significant modification of CCNG1 and PHPT1 transcriptional response in a dose- and time-dependent manner with opposite regulatory effects. Curcumin also affected CCNG1 and PHPT1 transcriptional response counteracting some of the radiation induction. No differences were observed based on sex. Dose estimations calculated using linear regression were affected by lipopolysaccharide and curcumin. In conclusion, several confounding factors tested in this study can indeed modulate the transcriptional response of CCNG1 and PHPT1 and consequently can affect radiation exposure dose estimations but not to a level which should prevent the biomarkers' use for triage purposes.